Ag-coated one-dimensional orthorhombic Nb2O5 fibers as high performance electrodes for lithium storage. (10th April 2018) - Cheong, Jun Young; Youn, Doo Young; Kim, Chanhoon; Jung, Ji-Won; Ogata, Alana F.; Bae, Jin Gook; Kim, Il-Doo
Abstract: In the recent times, pseudocapacitive electrode materials have received great attention due to their considerable capability in storing ions at relatively fast charging rates. Among various candidates, niobium (V) pentoxide (Nb2 O5 ) has gained much attraction for lithium-ion batteries (LIBs) due to its insertion/extraction reaction with Li, safe redox potential, and considerably good capacity (about 200 mAhg −1 ). Nevertheless, low conductivity of Nb2 O5 has so far prevented its use as a viable electrode material for LIBs. In this study, we have successfully coated silver (Ag) nanoparticles (NPs) on the surface of one-dimensional orthorhombic Nb2 O5 fiber (1D T-Nb2 O5 ) using simple electrospinning processing. Ag NPs coated Nb2 O5 fibers (Ag-1D T-Nb2 O5 ) provided faster electron pathways, resulting in much improved capacity at a given current density with superior rate capabilities compared with pristine 1D T-Nb2 O5 . In addition, 1D T-Nb2 O5 was more suitable for coating Ag NPs compared with T-Nb2 O5 NPs, where its structural integrity was maintained even after cycling. As a result, effective coating of conductive Ag NPs on the 1D T-Nb2 O5 resulted in excellent cycle retention characteristics (179.7 mAhg −1 after 500 cycles at 500 mA g −1 ) as well as superior rate capabilities (103.6 mAhg −1 at a current density of 5000 mA g −1 ). Graphical abstract: Highlights: Ag NPs were decorated on 1D T-Nb2 O5 . Decoration of Ag NPs resulted in enhanced reversible capacity. Ag-1D T-Nb2 O5 exhibited excellent rate capabilities. 1D T-Nb2 O5 served as effective platforms for decoration of Ag NPs. The structural integrity of Ag-1D T-Nb2 O5 was maintained after cycles.